An Exploratory Study on Korean National Taekwondo Competitors' Imagery Strategy based on Their Preparation Periods - Tae-Jin Son; Inchon Park (Korea Institute of Sport Science, 2022)
This study aimed to explore elite taekwondo competitors' imagery strategies . The study participants were 10 elite taekwondo athletes, who worked for S business team. Data were collected through open-ended questionnaires and in-depth interviews. The data were collected based on Gould et al. (1992)'s proposed qualitative research method. The inductive content analysis of the imagery was conducted following the imagery type of Paivio (1985) and Suinn (1996). The law data and case of imagery were separated by three specialists. The results were as follows. First, elite taekwondo competitors generally used the types of imagery proposed by Paivio (1985) and Suinn (1996). In particular, imagery of anxiety regulation appeared with the highest frequency among factors and ordered imagery of motivation, imagery of skills, imagery of mental skills, and imagery of competition. Second, elite taekwondo competitors mainly used imagery of skills before two weeks for competition. They mainly used imagery of anxiety regulation the day before a competition. They used imagery of anxiety regulation and imagery of motivation on the day of a competition. They used imagery of motivation after the competition. In sum, elite taekwondo competitors used individual strategies in terms of imagery in order to ensure effective training and peak performance in competition. The strategy of imagery was applied differently based on the juncture of the competition.